1993
DOI: 10.1007/bf00201354
|View full text |Cite
|
Sign up to set email alerts
|

Cell-wall development in freeze-fixed pollen: Intine formation of Ledebouria socialis (Hyacinthaceae)

Abstract: Abstract. The structure and development of the inner pectocellulosic pollen wall, the intine, was re-examined using high-pressure freezing with subsequent freeze substitution in Ledebouria socialis Roth, a monocotyledonous angiosperm. The bilayered intine is formed immediately after differentiation of the endexine. Similar to somatic cell walls, intine matrix substances originate from the Golgi apparatus and leave the cytoplasm via exocytosis. Exintine development starts with the apposition of intine matrix su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…3). Microtubules were observed during all developmental stages but we failed in detecting microfilaments (for detailed discussions see Ding et al 1992;McCauley and Hepler 1992;Meindl et al 1992;Hess 1993). (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…3). Microtubules were observed during all developmental stages but we failed in detecting microfilaments (for detailed discussions see Ding et al 1992;McCauley and Hepler 1992;Meindl et al 1992;Hess 1993). (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…High-pressure freezing and FS were performed according to Studer et al (1989) as previously reported (Hess 1993;Hess and Glaser 1993). Briefly, intact anthers were cryoimmobilized using a highpressure freezer (HPM 010; Balzers Union, Liechtenstein).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Last but not least, specimens with an almost impermeable coat such as C. elegans or plant pollen are practically impossible to preserve by direct aldehyde Wxation. After high pressure freezing and freeze substitution, however, their ultrastructure is beautifully preserved (Hess 1993;Hohenberg et al 1994;McDonald and Morphew 1993).…”
Section: Structural Preservation Of High Pressure Frozen Versus Chemimentioning
confidence: 99%